Biocontrol Analysis of Trichoderma sp. as endophytic fungi for potential bioinsecticide against Thrips - Aidha Zulaika; Darmono Taniwiryono; Sari Sekar Ningrum; Revi Meliyani; Efnur Ernaldi (Universitas Ibn Khaldun Bogor, 2024)
Thrips is a pathogen insect that commonly attacked crop plant. Tomato and chili are essential crop plant in indonesia. In order to tackle this problem not only environmentally friendly but also in sustainability aspects, bioinsecticide agent are explored. This study aims to explore Trichoderma as endhopytic fungi with bioinsecticide ability. The experiment design to test Trichoderma Thrips in aclimatisation test for tomato and chili plant. The result in controling test against Thrips, T. DT 38 and T koningii was the best resistence while T harzianum B was the worst. This isolate can help slowing the effect of Thrips invasion. Based on that Trichoderma approved has bioinsecticide ability against Thriips invasion. But for effective implementation, formulation and perfection microbial isolate are needed.